Case Report: Preemptive Treatment With Low-Dose PD-1 Blockade and Azacitidine for Molecular Relapsed Acute Myeloid Leukemia With RUNX1-RUNX1T1 After Allogeneic Hematopoietic Stem Cell Transplantation - Tang, Yutong; Zhou, Zhenyang; Yan, Han; You, Yong (Frontiers in Immunology, 2022)
Acute myeloid leukemia (AML) patients who develop hematological relapse (HR) after allogeneic hematopoietic stem cell transplantation (allo-HSCT) generally have dismal clinical outcomes. Measurable residual disease (MRD)-directed preemptive interventions are effective approaches to prevent disease progression and improve prognosis for molecular relapsed patients with warning signs of impending HR. In this situation, boosting the graft-vs-leukemia (GVL) effect with immune checkpoint inhibitors (ICIs) might be a promising prevention strategy, despite the potential for causing severe graft-vs-host disease (GVHD). In the present study, we reported for the first time an AML patient with RUNX1-RUNX1T1 who underwent preemptive treatment with the combined application of tislelizumab (an anti-PD-1 antibody) and azacitidine to avoid HR following allo-HSCT. On day +81, molecular relapse with MRD depicted by RUNX1-RUN1T1-positivity as well as mixed donor chimerism occurred in the patient. On day +95, with no signs of GVHD and an excellent eastern cooperative oncology group performance status (ECOG PS), the patient thus was administered with 100 mg of tislelizumab on day 1 and 100 mg of azacitidine on days 1-7. After the combination therapy, complete remission was successfully achieved with significant improvement in hematologic response, and the MRD marker RUNX1-RUNX1T1 turned negative, along with a complete donor chimerism in bone marrow. Meanwhile, the patient experienced moderate GVHD and immune-related adverse events (irAEs), successively involving the lung, liver, lower digestive tract and urinary system, which were well controlled by immunosuppressive therapies. As far as we know, this case is the first one to report the use of tislelizumab in combination with azacitidine to prevent post-transplant relapse in AML. In summary, the application of ICIs in MRD positive patients might be an attractive strategy for immune modulation in the future to reduce the incidence of HR in the post-transplant setting, but safer clinical application schedules need to be explored.